Opening Press Conference, World Bank/IMF Annual Meetings, Lima, Peru, October 8, 2015 - Kim, Jim Yong (2016)
This is the transcript of the remarks delivered by Jim Yong Kim, President of the World Bank Group. He discusses on the period of slow growth, the end of the commodity super-cycle, pending interest-rate hikes, and the continued flight of capital out of emerging markets in the world. He talks about governments that must overcome a growing demographic divide to make future progress. He talks about the climate change and the need to cut emissions and invest in greater resilience . He speaks about developing countries that are going to get serious about increasing tax revenues, and stopping illicit flows of money. He mentions about the increase of capacity to support countries all over the world in building successful Purchasing Power Parity (PPP). He concludes by talking about Mexico and its very rapid development in the northern states and the need to apply that model for the development of southern states.